Evaluation of an improved CFD model against nine vented deflagration experiments. (31st March 2021) - Tolias, I.C.; Venetsanos, A.G.; Kuznetsov, M.; Koutsoukos, S.
Abstract: In the present work, a newly developed CFD deflagration model incorporated into the ADREA-HF code is evaluated against hydrogen vented deflagrations experiments carried out by KIT and FM-Global in a medium (1 m 3 ) and a real (63.7 m 3 ) scale enclosure respectively. A square vent of 0.5 m 2 and 5.4 m 2 respectively is located in the center of one of side walls. In the case of the medium scale enclosure the 18% v/v homogeneous hydrogen-air mixture and back-wall ignition case is examined. In the case of the real scale enclosure the examined cases cover different homogeneous mixture concentrations (15% and 18% v/v), different ignition locations (back-wall and center) and different levels of initial turbulence. The CFD model accounts for flame instabilities that develop as the flame propagates inside the chamber and turbulence that mainly develops outside the vent. Pressure predictions are compared against experimental measurements revealing a very good performance of the CFD model for the back-wall ignition cases. For the center ignition cases, the model overestimates the maximum overpressure. The opening of the vent cover is identified as a possible reason for the overprediction. The analysis indicates that turbulence is the main factor which enhances external explosion strength causing the sudden pressure increase, confirming previous findings. Highlights: Evaluation of a newly developed CFD deflagration model. Hydrogen vented deflagration experiments of KIT and FM-Global are analyzed. Back and central ignition cases with or without initial turbulence are examined. Simulations predict turbulence development outside the vent. Overall, satisfactory performance of the CFD model.